Handling and reporting of nephrectomy specimens for adult renal tumours: a survey by the European Network of Uropathology. Issue 2 (30th September 2011) - Algaba, Ferran; Delahunt, Brett; Berney, Daniel M; Camparo, Philippe; Compérat, Eva; Griffiths, David; Kristiansen, Glen; Lopez-Beltran, Antonio; Martignoni, Guido; Moch, Holger; Montironi, Rodolfo; Varma, Murali; et al.
Abstract : Aim: To collect information on current practices of European pathologists for the handling and reporting of nephrectomy specimens with renal tumours. Methods and Results: A questionnaire was circulated to the members of the European Network of Uropathology, which consists of 343 pathologists in 15 European countries. Replies were received from 48% of members. These replies indicated that nephrectomy specimens are most often received in formalin. Lymph nodes are found in less than 5% of nephrectomy specimens. All respondents give an objective measure of tumour size, most commonly in three diameters. The most common method to search for capsule penetration is to slice tissue outside the tumour perpendicularly into the tumour. The most common sampling algorithm from tumours greater than 2 cm is one section for every centimetre of maximum tumour diameter. Most respondents use the 2004 WHO renal tumour classification although only slightly over half consider small papillary tumours malignant if the diameter is greater than 5 mm. The Fuhrman grading system is widely used. Almost all use immunohistochemistry for histological typing in some cases, while only 7% always use it. The most utilised special stains are CK7 (95%), CD10 (93%), vimentin (86%), HMB45 (68%), c-kit (61%) and Hale's colloidal iron (52%). Only 18% use other ancillary techniques for diagnosis in difficult cases. Conclusions: While most pathologists appear to follow published guidelines for reporting renal carcinoma, there is still a need for the development of consensus and further standardisation of practice for contentious areas of specimen handling and reporting.